A diffusion model approach to analysing the bilingual advantage for the Flanker task: The role of attentional control processes. (August 2017) - Ong, Gabriel; Sewell, David K.; Weekes, Brendan; McKague, Meredith; Abutalebi, Jubin
Abstract: Elderly bilingual speakers exhibit a response time (RT) advantage on tests of executive function such as the Flanker task. There is, however, a lack of consensus regarding the cognitive mechanisms underlying this bilingual advantage . We analysed Flanker task performance from elderly bilingual (N = 29, age range = 55–75) and monolingual (N = 27, age range = 53–75) speakers using Ratcliff's (1978) diffusion model, which conceptualizes decision-making as a stochastic evidence accumulation process governed by parameters with empirically validated psychological interpretations. These parameters were analysed to investigate differences in cognitive processing between bilingual and monolingual groups in flanker RT performance. A bilingual advantage on decision making onset (the non-decision time parameter) was observed. Non-decision time was shorter on incongruent flanker trials for bilingual speakers but other parameters relating to quality of evidence (drift rate) and decision criterion (boundary separation) did not differ between groups. We interpret this non-decision time cost as reflecting a process of attentional 'filtering out' of distracting information. We therefore contend that lifelong bilingual language experience generates enhanced attentional control for seniors. Highlights: The study investigates the bilingual advantage on a flanker task. RT distributions are analysed with the diffusion model. There is an interaction between bilingualism and trial type on non-decision time. Attentional processing is implicated in the bilingual advantage.